1992
DOI: 10.1007/bf00119297
|View full text |Cite
|
Sign up to set email alerts
|

Limitations of the scrape-loading/dye transfer technique to quantify inhibition of gap junctional intercellular communication

Abstract: Gap junctional intercellular communication (GJIC) is recognized as playing an important role in normal cell proliferation and development. Chemically induced alteration of GJIC has been proposed to be associated with abnormal cellular growth and/or tumor promotion. Several in vitro assays are currently used to determine the effects of chemicals on GJIC between cultured mammalian cells. One of these assays, the scrape-loading dye transfer (SL/DT) technique, is based on monitoring the transfer of the fluorescent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Mckarns and Doolittle (1992) compared different methods and proposed the use of SL/DT only to determine the qualitative presence or absence of GJIC. In contrast, Opsahl and Rivedal (2000) had compared the use of both SL/DT and microinjection as tools for GJIC quantification and they had demonstrated that scrape loading combined with image analysis can even offer advantages on the microinjection.…”
Section: Resultsmentioning
confidence: 99%
“…Mckarns and Doolittle (1992) compared different methods and proposed the use of SL/DT only to determine the qualitative presence or absence of GJIC. In contrast, Opsahl and Rivedal (2000) had compared the use of both SL/DT and microinjection as tools for GJIC quantification and they had demonstrated that scrape loading combined with image analysis can even offer advantages on the microinjection.…”
Section: Resultsmentioning
confidence: 99%
“…7). Because scrape-loading is a qualitative method, quantitative comparisons were not made [37]. The dye-coupling experiments suggest that endometrial stromal cells develop functional gap junctions early during culture (3 h) and that they remain present throughout the culture period (up to 72 h).…”
Section: Discussionmentioning
confidence: 99%
“…Disruption of gap junctional communication can be measured by intercellular transfer of the dye Lucifer yellow following application of the tumor promoter 12-O-tetradecanoylphorbol-13-acetate (TPA) (McKarns and Doolittle, 1982). A study by Kang et al (1996) showed that noncytotoxic concentrations of TT inhibited GJIC in normal human breast epithelial cells in a dose-dependent way after 90 min of exposure.…”
Section: Toxaphene As a Tumor Promotermentioning
confidence: 99%
“…This dye has been used for a number of years to observe disruption of gap junctional communication and electrical junctions between nerve cells. (e.g., McKarns and Doolittle, 1982;Spencer and Satterlie, 1980). 2,3,7,8-TCDD was used as a positive control.…”
Section: In Vitro Study Of Gap Junctional Intercellular Communicationmentioning
confidence: 99%